Comprehensive Approach to Diabetic Neuropathy - A Review of the Latest Reports - Hajduk-Maślak, Katarzyna; Skóra, Adrianna; Galasińska, Iwona; Michalik, Beniamin; Szypuła, Aleksandra; Sęk, Michał (Journal of Education, Health and Sport, 2024)
Neuropathy is a damage, disease, or dysfunction of one or more nerves especially of the peripheral nervous system. One of the most common disease causing neuropathy is diabetes mellitus. Diabetic neuropathy is a serious consequence that arises when nerve tissue is damaged by prolonged hyperglycemia. It affects a considerable portion of those who have the disease. This article covers every component of this complexed disease. We will discuss the definition, etiology, risk factors that patients can control and that are uncontrollable, and forms of neuropathies linked to diabetes such as peripheral, autonomic and focal. For more clinical approach signs and symptoms, diagnostic methods which are a mix of clinical evaluations, neurological exams, electrophysiological testing, and, in certain situations, imaging modalities and complicated nature of treating diabetic neuropathy will be explored. Moreover, challenges in treating this disease and future directions and research will be elaborated. What is more it interdisciplinary care will be explored as a key element in addressing complexed nature of diabetic neuropathy. In addition to highlighting the complexity of neuropathy in diabetes mellitus and emphasizing the vital significance of early recognition and specialized interventions for the best possible patient outcomes, the article aims to present a thorough grasp of diabetic neuropathy.